Uncovering school-level influences on equal educational opportunities in secondary education: a systematic review of the interplay among key factors - Katrien Hermans; Liesbet Saenen; Elke Emmers; Katrien Struyven (Frontiers in Education)
Schools play a fundamental role in fostering both academic and personal development, ensuring equal educational opportunities (EEO). Despite this ambition, education remains an institution that reproduces inequality, particularly at the secondary school level. Research on educational inequalities has mainly focused on individual pupil and/or teacher factors, neglecting the broader school environment. This systematic literature review (SLR) addresses this gap by identifying how school-level factors influence EEO. The literature review included 14 studies, of which eight were qualitative, three were quantitative and three were mixed methods studies. The review adhered to the PRISMA guidelines and a thematic analysis was performed. The findings reveal a notable gap in research addressing how various factors—such as teachers’ attitudes, pupil grouping and school culture—interplay in ensuring EEO. Moreover, the findings underscore the importance of school leadership in navigating and facilitating this interplay. This systematic review highlights the need for future research to adopt an integrated and comprehensive approach in order to gain deeper, qualitative insights into how these factors work together to foster equal educational opportunities.